MANAJEMEN PORTOFOLIO SEBAGAI STRATEGI KEBERHASILAN PROYEK TEKNOLOGI INFORMASI - Setiawan, Herri; N, Ashari S (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
IT project portfolio managementis acomplex phenomenonin portfolio manage-mentasanew concept of knowledge management.Projects whichare toorestricting the us-age of resources without a risk calculation will be have effect to expectations ofthe success of a project.Strong leadership is needed to overcome these barriers, facilitating the new processes, and create a portfolio of projects with appropri at managemment. Knowledgeand understanding of the importance of project portfolio management especially in IT projects is required.The study discusses the descriptionof information technology project portfolio management, portfolio management models, problems and benefits of the implementation of IT project portfolios. The results explain several methods for calculating the economic value ofthe project and the steps in determining the selection of projects based on the constraints specified on IT project.